MOTIF PENGGUNAAN APLIKASI TIKTOK PADA MAHASISWA PROGRAM STUDI ILMU KOMUNIKASI ANGKATAN 2019 UNIVERSITAS MULAWARMAN - Kamilah, Nazrah; Purwanti, Silviana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Technological capabilities in the current era are very advanced as a result of the times. One form of technological development that is currently widely used by all groups including students is the TikTok application. This study aims to determine how the motives for using the TikTok application in students of the Communication Science Study Program Class of 2019, Mulawarman University. This research uses a qualitative method with a phenomenological approach and uses the Uses and Gratification theory. The techniques used in collecting data are observation, interviews, and documentation. There are three informants obtained through purposive sampling technique. Data processing in this study used data analysis techniques from Matthew B. Miles and Michael Huberman. Based on the results of the study, the motives that encourage the use of the TikTok application by students of the Mulawarman University Communication Science study program are relevant to the theory of media use motives expressed by McQuail, that there are four motives that become the reasons and encouragement of students choosing to use the TikTok application, namely diversion motives, personal relationship motives, personal identity motives, and surveillance motives. With the results showing that the dominant motive for using the TikTok application is as a diversionary motive related to the desire to escape from daily problems, release work fatigue, and the desire to seek entertainment or diversion.